PROFIL PERKEMBANGAN SOSIAL SISWA TERISOLASI DALAM MEMBINA HUBUNGAN SOSIAL KELAS XI SMA NEGERI 12 PADANG - Lovita, Yulia Ningsih; Said, Azrul; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
ABSTRACTThis research conducted by the phenomena that occur in the field which the students is individual who are experiencing social development, the social development of the students peer, however, studies look at the students who are isolated, therefore researcher raised this issue to be researched with the title profile of social development students isolated in the social relations at class XI of SMAN 12 Padang. The purpose of this research is to see: 1) profile of social development studentsâ isolated in the social relations friendship in peers. 2) Profile of social development studentsâ isolated with connection peers in studied. Type of this research is descriptive research the purpose to describe with detail. Subject of this research is students isolated at class XI total 84 students. Tool of collector data is questionnaire. Although the technic of data analysis that used is percentage formula. The result this research indicate that: 1). Profile of social development studentsâ isolated in the social connection friendship in peers not good. 2) Profile of social development students isolated in connection peers in studied not good.